Undergraduates’ entry requirements and student personal variables as determinants of academic performance in Faculty of science, University of Ibadan (2020)
First year university undergraduates' performance has not been in tandem with achievement in entry requirements (Senior Secondary Certificate Examinations results, scores in Unified Tertiary Matriculation Examinations and Post-Unified Tertiary Matriculation Examination). Thus, undergraduates with good grades in SSCE results, high scores in UTME and Post-UTME lost their admissions due to poor performance in their first-year examinations. Past studies on causes of poor performance have focused largely on assessing the cognitive domain with little attention paid to students' other personal variables: interest in university education, mental ability, career aspiration and gender. This study examined the adequacy of the entry requirements students' personal variables and academic candidates' capability in determining first year students' performance in the Faculty of Science, University of Ibadan. Purposive sampling technique was used to select six out of the eleven departments in the faculty. The instruments used were Undergraduates' Career Aspiration, Undergraduates' Interest in University Education^ Questionnaires and Mental Ability Test. Data were analysed using path coefficients at p < 0.05 level of significance and covariance based structural equation modelling. Modelling the variables revealed that 9 out of 27 paths were significant and true predictors of undergraduates' academic performance in the first academic year. While the direct and indirect path coefficients of mental ability on academic achievement were not significant and consequently eliminated from the model. Interest in university education, career aspiration, gender alongside performance in SSSE, UTME and Post-UTME were important in determining academic performance of first year science undergraduates in the University of Ibadan. Therefore, criterion on students' personal variables should be included in assessing candidates' capability for academic study.